Jednostavni glagolski oblici u temporalu Drugoga beramskoga brevijara - Zubčić, Sanja (2020)
U radu se analizira morfologija jednostavnih glagolskih oblika u temporalu Drugoga beramskoga brevijara: prezenta, sintetskoga imperativa, imperfekta i aorista. Podatci se uspoređuju sa stanjem opisanim u liturgijskim tekstovima pisanim hrvatskim crkvenoslavenskim jezikom. Pozornost se posvećuje i onim značajkama koje predstavljaju odstupanja od norme hrvatskoga crkvenoslavenskoga jezika i koje su u tekstove ušle iz govorne čakavštine. Radom će se pridonijeti cjelovitijem poznavanju morfologije jednostavnih glagolskih oblika u hrvatskom crkvenoslavenskom jeziku, a ekscerpirani će govorni, čakavski elementi moći poslužiti pri utvrđivanju tempa promjena u hrvatskom jeziku.
This paper analyses the morphology of simple verb forms in the Proprium de tempore of the Second Beram Breviary: present, synthetic imperative, imperfect, and aorist. The data is compared with descriptions in Croatian Church Slavonic liturgical texts, including those features that, being introduced from vernacular Chakavian, deviate from the norm of Croatian Church Slavonic. The analysis has shown that the morphology of simple verb forms in the Proprium de tempore of the Second Beram Breviary is mostly consistent with the norm of Croatian Church Slavonic, with all listed deviations also being confirmed in other liturgical texts. Divergent elements most commonly originate from vernacular Chakavian or are the result of paradigmatic alignment. The category of the dual is still well preserved, and systematic alignment resulting in final -ta is found in the 2nd and 3rd person. The present forms of thematic verbs are found to occasionally deviate in the 1st person sg. and 3rd person sg. and pl., while the most frequent innovation from spoken language is the ending -mo, although forms with the older ending -mь/-mʼ/-m are the most prevalent. In the present tense of athematic verbs the ending -ši is confirmed to have spread in the 2nd person sg. of the verbs êsti (ʻeatʼ), dati (ʻgiveʼ) and vêdêti (ʻseeʼ), while innovations in the 3rd person sg. and the unstressed form of the verb biti (ʻbeʼ) are found in the rubrics. The 3rd person pl. is confirmed to end in final -tь, with the ending -utь having spread as a result of alignment with thematic verbs. The endings of the synthetic imperative plural tend to be aligned. Despite examples of reciprocal alignment in the Proprium de tempore of the Second Beram Breviary, alignment of e-type verbs according to endings with the formant i is more common than vice versa.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 186-188.
Sažetak ; Summary.
Keywords: Drugi beramski brevijar -- Morfologija -- Glagolski oblici -- Liturgijski tekstovi